2019
DOI: 10.3390/rs11141675
|View full text |Cite
|
Sign up to set email alerts
|

Semi-Automatic Identification and Pre-Screening of Geological–Geotechnical Deformational Processes Using Persistent Scatterer Interferometry Datasets

Abstract: This work describes a new procedure aimed to semi-automatically identify clusters of active persistent scatterers and preliminarily associate them with different potential types of deformational processes over wide areas. This procedure consists of three main modules: (i) ADAfinder, aimed at the detection of Active Deformation Areas (ADA) using Persistent Scatterer Interferometry (PSI) data; (ii) LOS2HV, focused on the decomposition of Line Of Sight (LOS) displacements from ascending and descending PSI dataset… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 37 publications
0
39
0
5
Order By: Relevance
“…In the case of ADAfinder, the methodology to perform the identification and assessment of ADA was presented in [26,27] back in 2017 and 2019, respectively. In these works, the authors explain in detail the procedure to identify the active deformation areas and to assess their quality.…”
Section: Adatoolsmentioning
confidence: 99%
“…In the case of ADAfinder, the methodology to perform the identification and assessment of ADA was presented in [26,27] back in 2017 and 2019, respectively. In these works, the authors explain in detail the procedure to identify the active deformation areas and to assess their quality.…”
Section: Adatoolsmentioning
confidence: 99%
“…Many studies have shown the use of the DInSAR methodology to assess the ground deformation [ 6 , 7 , 8 , 9 ]. Over the past few years, a lot of effort has been put in the automation of DInSAR [ 10 , 11 , 12 ] or PSInsar procedures [ 13 ]. The development of an effective method of automatic detection of deformation patterns in the SAR interferograms is difficult due to the presence of noise and irregularities.…”
Section: Introductionmentioning
confidence: 99%
“…Since seismic, volcanic and flood vulnerability has been widely studied, geological risks associated to local or slow processes are still underdeveloped. Recent studies focused on landslides and rockfalls, developing methodologies that generate useful products for local authorities derived from remote sensing data [ 12 , 27 , 28 , 29 , 30 , 31 ]. Land subsidence is characterized by slow displacements that usually cover large areas and involve agricultural and economic activities as well as buildings, cultural heritages and linear infrastructures, generating important economic losses.…”
Section: Introductionmentioning
confidence: 99%